Deconstructing Marketing: How Should We Approach Marketing in the New Economy? - María Elena Rodríguez Benito (European Scientific Journal, ESJ, 2019)
As a business function, marketing generates strong resistance within both consumers and companies that favour sustainable consumption and development, so we want to figure out how marketing should evolve to fit into this new economic scheme. In this article, we will analyse the experiences and main conclusions of a focus group about how should business approach marketing in the new economic models. For this, we will first conceptualize both the new economic models and the marketing criticism, as well as the focus group as a qualitative research tool that can help us to frame broader research. We want to highlight the methodology of doing a focus group during a conference as well as the benefits of conducting such a group. The discussion of the focus group brings up two important issues: (a) the green gap in consumers, and (b) the fundamental differences between green and sustainable consumption and, consequently, between green and sustainable marketing. We will analyse the main territories opened during the research, which will help us define a marketing model aligned with the new economies during further research. Our analysis will explore the importance of vocabulary for the perception of marketing, the fact that marketing should be created within the community, or the necessity to create a marketing model using a systemic consensus.